Viability and germination in creole corn seeds from the state of Guerrero - Escobar-Álvarez, José Luis; Ramírez-Reynoso, Omar; Cinsteros Saguilán, Pedro; Gutiérrez-Dorado, Roberto; Maldonado-Peralta, María de los Ángeles; Valenzuela -Lagarda, José Luis (Ecosistemas y Recursos Agropecuarios, 2021)
Mexico is considered in the center of origin of corn, due to the variability of genotypes that have been identified and morphologically identified. It currently has 64 races, and in the State of Guerrero 15 races have been identified. The objective of this study was collected in plots of small producers four creole varieties and compare the quality of seed that they harvest and conserve for the establishment use in the establishment of their plots The variables evaluated were imbibition kinetics, percentage of humidity, percentage of standard germination, rate and coefficient of germination speed, and viability. A completely randomized design will be needed and with the data obtained from the variables, a homogeneity test was continued; As the data were normal, and significant differences were found between the means of the treatments, a Tukey test (p ≤ 0.05) was performed with the SAS statistical program. Regarding the rate of imbibition, the creole Punta Cuata presented a higher percentage of absorption, for the percentage of germination there is no statistical difference (p = 0.4411), with Morado and Olotillo experiencing greater speed in germinating and the four creoles had a viability greater than 98 % The seed quality of the creole varieties evaluated in this study has a high capacity for reproduction and conservation.